News Construction of COVID’s Crisis Management of Indonesian Government through Detik.com - Prayudi Prayudi; Virginia Ayu Sagita (Jurnal Ilmu Komunikasi, 2021)
The COVID-19 pandemic has hit all parts of the world. This led to crises in various governments regarding how the government deals with the effects of this virus. This study aims to analyze the text of the Indonesian government’s crisis communication news in the face of the COVID-19 issue in the online media Detik.com. The research method used is qualitative research with a textual analysis approach. The results showed that Detik.com reports the problem straightforwardly. Detik.com maintains a firm editorial policy and commits to presenting an even-handed and fair view of issues. Detik.com seeks to reveal how the Government responded at the start of the crisis, government policies during the crisis, and how the public responded to government policies. This research shows how online media in Indonesia constructed news on Indonesian government crisis communication in handling the COVID-19 pandemic. The substance of this research contributes in the form of new policy recommendations for online media news leaders to deliver news openly, straightforwardly, and critically that prioritizes social responsibility to the public.